2019
DOI: 10.1111/hsc.12776
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of positive mental health programs in adults: A systematic review

Abstract: A systematic review was conducted. So, electronic database including CINAHL, Embase, MEDLINE, Pubmed, Scopus and Cochrane‐Central were explored in January 2017 and in October 2017. The aim of this systematic review is to identify, appraise and synthesize the best evidence for the effectiveness of programmes of positive mental health in adults. Mental health is regarded as an ideal functioning state of the human being, which emphasizes the relevance of promoting the person's qualities in the optimization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 24 publications
(62 reference statements)
2
24
0
1
Order By: Relevance
“…These data are in accordance with previous studies [15,16,18,19] that linked knowledge to the possibility of taking action to benefit one's health and the health of other persons, which in turn showed that mental health literacy has several components [10]. As stated in the definition of Positive Mental Health, this possibility of knowledge leads to action and enhances a person's capacity to optimize PMH factors that require more attention and/or maintain optimum levels of PMH [1].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These data are in accordance with previous studies [15,16,18,19] that linked knowledge to the possibility of taking action to benefit one's health and the health of other persons, which in turn showed that mental health literacy has several components [10]. As stated in the definition of Positive Mental Health, this possibility of knowledge leads to action and enhances a person's capacity to optimize PMH factors that require more attention and/or maintain optimum levels of PMH [1].…”
Section: Discussionsupporting
confidence: 91%
“…In this way, pathological outbreaks can be avoided when people experience ineffective transitions or daily setbacks. Programmes that promote PMH can be found in the literature [1], and free smartphone apps that improve PMH levels already exist [19]. In addition, schools are privileged environments to equip students with strategies to promote positive mental health [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the caregiver’s role is an important element in ensuring the well-being of the person being cared for [ 11 ], intervention in this population group becomes a priority. There are intervention and/or support programs that have been positively evaluated [ 12 - 15 ], although most of them are based on in-person training. However, research has shown that many caregivers underutilize the supports available to them and instead try to handle everything by themselves [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%